Implementing an environmental DNA/RNA-based approach to non-invasively investigate disease caused by Ichthyophthirius multifiliis - Yajiao Duan; Moonika Haahr Marana; Hannah Malene Jensen; Cyril Henard; Louise von Gersdorff Jørgensen (Aquaculture Reports)
Infectious diseases impose a substantial burden on aquaculture, acting as a significant constraint on production yields, entailing considerable management costs. White spot disease, which is caused by the protozoan fish parasite, Ichthyophthirius multifiliis (Ich), is a good example of a disease which continuously cause major challenge for the aquaculture worldwide. Utilization of environmental DNA/RNA (eNA) extracted from fish water for pathogen detection and quantification offers a potentially non-invasive and routine strategy for monitoring diseases in aquaculture systems. In this experimental study, rainbow trout (Oncorhynchus mykiss) were challenged with Ich in two concentrations. The eNA was extracted from the tank water and was used to detect the parasite throughout the course of the disease targeting a gene encoding an Ich immobilization antigen (Iag52a). Simultaneously, the parasite burden and immune-relevant gene expression in both water and fish gills were investigated. The results showed that the level of Ich eNA exhibited a peak at the onset of mortality at 10 days post challenge (dpc), decreasing at 12 dpc. Most immune relevant genes expressed in the gills were downregulated at 2 dpc and upregulated at 8 dpc. The gene expression of two acute phase proteins from the host, Serum amyloid A (SAA) and Hepcidin, were investigated both in the gills and in the water. The two genes were downregulated in water at 10 dpc, coinciding with the peak mortality time point and the highest parasite eNA load in the water. This study provides an insight into the pathogen eNA dynamics where a Ct value of 18–25 of iag52a indicated critical disease outbreak.